Pemberdayaan Kaum Du’afa dalam Perspektif Al-Quran - Riza Awal Novanto; Toto Santi Aji (AL-MUFASSIR, 2021)
The present study aims to investigate the empowerment of dhuafa (poor people) based on the perspective of Al-Qur’an. According to the standpoint proposed inside the Al-Qur’an, poverty is deemed as a community concern that has to be fixed. Al-Qur’an as Muslims’ ways of life can indeed answer all these concerns and problems particularly in liberating and empowering dhuafa. The emergence of dhuafa is inevitably a life reality. Therefore, it is crucial to scrutinize the viewpoint of Al-Qur’an concerning the empowerment of dhuafa. There are several efforts initiated to lessen poverty and empower them based on the Al-Qur’an’s perspective specifically the calls for living a life, the calls for giving, the calls for fulfilling alms, the calls for inheritance settlement, the calls for the prohibition of usury, monopoly (ihtikar), and hoarding assets (iktinaz).